Evaluation of SAR Distribution in Six-Layer Human Head Model - Asma Lak; Homayoon Oraizi (International Journal of Antennas and Propagation)
The interaction between human head model and electromagnetic field sources is studied. The head models are composed of one and six layers. The six layers are skin, fat, bone, dura (the outer membrane of brain and spinal cord), CSF (colony stimulating factor), and brain. An antenna as a source of exposure is simulated too. The E-field strength distribution in both one- and six-layer human models is shown to estimate the intensity of E-field penetration in human head. Like standard models, the antenna is situated near the head model at a distance of 5 mm. The local and average SARs (specific absorption rates) are simulated at 900 MHz in both human head models. The results are then compared between the two models. The HFSS software is used for all the simulations. The paper wants to show that the initial model (one layer) is not a good model, because the real human head tissue is not equivalently modeled. It seems that the values of one-layer model are not reliable, so the paper considers the better and more similar human head model and compares these two models.